Mesenchymal hamartoma of the liver - Akbay, Y. Ziyaettin; Aykan, Talia Bali; Akün, Mehmet; Çorbacıoğlu, Doğan (The Turkish Journal of Pediatrics, 1966)
A case of mesenchymal hamartoma of the liver associated with a rapidly developing ascites in an eleven month old female infant is presented. Rapid enlargement of the abdomen and signs referable to a disturbance of the gastrointestinal tract were the first symptoms of the condition in the previously perfectly healthy appearing infant. Microscopically the lesion consisted largely of loose myxomatous connective tissue of fibroadenomatous structure with bile ducts and scattered areas of hepatic cells.It is stressed that tumors of the liver should be considered in differential diagnoses of abdominal syndromes.Hypotheses in the genesis of the hamartoma are briefly discussed in the light of present knowledge of embryonic development of intrahepatic bile ducts.